Persepsi Guru Sekolah Dasar Terhadap Projek Penguatan Profil Pelajar Pancasila - Cyntia; Zariul Antosa; Eddy Noviana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study was to collect positive feedback on the Pancasila student profile enhancement project program by teachers. Teachers are more likely to understand, plan, and implement the Pancasila student profile enhancement project if they have a positive opinion of the project. However, negative opinions can complicate the implementation of the Pancasila student profile enhancement project. This study aims to investigate the perceptions of elementary school teachers towards the Pancasila student profile enhancement project in Payung Sekaki District, Pekanbaru City. The method used is quantitative research with a descriptive approach, involving 120 teacher respondents who filled out a questionnaire containing 44 statements. The results showed that teachers' perceptions of this project were classified as very good, with an overall achievement percentage score of 81.52%. The highest indicator was "Faithful, Devoted to TYME and Noble Morals" with a percentage of 86.23%, while the lowest indicator was "Creative" with a percentage of 74.17%. These findings indicate that teachers support the implementation of the Pancasila student profile enhancement project as an effort to improve character, critical thinking skills, and introduction to local culture among students. This research is expected to provide constructive feedback to improve the implementation of the program.